EKSPERIMENTASI MODEL PEMBELAJARAN BERBASIS MASALAH (PBM) DAN PEMBELAJARAN BERBASIS MASALAH (PBM) DENGAN PENDEKATAN SAINTIFIK PADA MATERI BANGUN RUANG DITINJAU DARI KEMAMPUAN KOMUNIKASI MATEMATIKA SISWA KELAS VIII SMP NEGERI SE-KABUPATEN SRAGEN - Reka Pramukti; Budi Usodo; Sri Subanti (Jurnal Pembelajaran Matematika, 2015)
Abstract : The aim of the research was to determine the effect of learning models on mathematics achievement viewed from mathematic communication ability. The learning model compared were direct, PBM with scientific approach, and PBM. This was quasi-experimental research with 3x3 factorial design. The population were all students of Junior High School in Sragen. The samples are the students of SMPN 2 Gemolong, SMPN 1 Kedawung, and SMPN 2 Masaran, which taken by using stratified cluster random sampling technique. The instruments used were mathematics achievement test and mathematic communication ability test. The data analysis technique was used unbalanced two ways anova. Based on the data analysis, it can be concluded as follows. (1) The students receiving PBM learning model with scientific approach and PBM learning model had better learning achievement than those receiving direct learning model. The students receiving PBM learning model with scientific approach had equal learning achievement to those receiving PBM learning model. (2) The students with high mathematic communication ability had better learning achievement than those with medium and low mathematic communication abilities. Those with medium mathematic communication ability had equal learning achievement to those with low one. (3) In each groups of student mathematic communication ability PBM learning model with scientific approach and PBM learning model provided better learning achievement than direct learning model, PBM learning model with scientific approach provided equal learning achievement to PBM learning model. (4) In each learning model, the students with high mathematic communication ability had better learning achievement than those with medium and low mathematic communication abilities. Those with medium mathematic communication ability had equal learning achievement to those with low one.Keywords: Direct  learning  model,  PBM  learning  model with scientific approach, PBM learning model, Mathematic Communication Ability.